Developing a training curriculum using professional learning community for enhancing teachers’ learning management skills to promote students’ creativity and innovation ability: a case study of Thai teachers - Patphol, Marut (Creativity Studies, 2022)
Thai primary school teachers must be developed learning management skills for promoting students’ creativity and innovation ability. This study developed a training curriculum to enhance teachers’ learning management skills to promote students’ creativity and innovation ability from using the professional learning community method and a training cycle “plan”, “do”, “check”, and “reflect”. There consisted three units of training curriculum, and the analytic scoring rubrics were used for collecting data. The results were (1) teachers’ learning management skills were higher after implementing the curriculum at a statistical significance level of .01, and (2) students’ creativity and innovation ability was higher after implementing the curriculum at the statistical significance level of .01.